1997
DOI: 10.1002/(sici)1096-9071(199702)51:2<132::aid-jmv8>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tumor necrosis factor levels in the serum and cerebrospinal fluid with clinical outcome in Japanese encephalitis patients

Abstract: To investigate the prognostic role of tumour necrosis factor (TNF) in Japanese encephalitis virus (JEV) infection, we measured the immunoreactive forms of TNF concentrations in the serum and cerebrospinal fluid (CSF) of 47 laboratory-confirmed cases of JE. It was observed that TNF levels were elevated (> 15 pgm/ml) in all the 47 serum samples (range 19.4-923.8 pg/ml), while in 46/47 CSF samples TNF was elevated (range 10.8-376 pg/ml). The mean (SD) TNF levels in the serum of fatal cases was 234.34 pg/ml (304.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 11 publications
3
58
0
1
Order By: Relevance
“…Similarly, adoptive transfer of monoclonal antibodies protected mice from lethal encephalitis caused by other flaviviruses, namely JEV [223], SLEV [224], and yellow fever virus [225]. Further, high levels of JEV-specific IgM and IgG in the CSF was linked to virus clearance from the CNS and a better clinical outcome in patients [226,227]. Development of nAbs was also associated with longer survival after intracerebral inoculation of mice with TBEV [208].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%
“…Similarly, adoptive transfer of monoclonal antibodies protected mice from lethal encephalitis caused by other flaviviruses, namely JEV [223], SLEV [224], and yellow fever virus [225]. Further, high levels of JEV-specific IgM and IgG in the CSF was linked to virus clearance from the CNS and a better clinical outcome in patients [226,227]. Development of nAbs was also associated with longer survival after intracerebral inoculation of mice with TBEV [208].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%
“…Local immune responses initiated by microglial cells may provide protection against JEV infection of the CNS. However, microglial activation resulting in elevated levels of proinflammatory cytokines (IL-6, TNF-, IL-1 ) and chemokines (IL-8, RANTES, MCP1) in the CSF and plasma may give rise to irreversible neuronal damage and correlates with an increased mortality rate Chen et al, 2010;Ghoshal et al, 2007;Ravi et al, 1997;Saxena et al, 2008;Winter et al, 2004).…”
Section: Cellular Factors Chemokines and Cytokinesmentioning
confidence: 99%
“…It has been well established that during viral infection, release of cytokines and chemokines by host immune cells play an important role in curtailing the infection. The cytokines either directly inhibit the virus or activate the cytotoxic T cells at the site of viral replication (8,9). It has also been shown that cytokines, apart from modulating immune response and inflammatory reaction, also have direct cytotoxic effects, most notable among these being interleukin (IL)-1 and tumor necrosis factor (TNF) (10).…”
mentioning
confidence: 99%